Community Service Programs for Serundeng and Marine Fish Chili Crafts Community with Local Expertise to Encourage Entrepreneurial Innovation and Competitiveness in Kenjeran, Surabaya - Suhud Wahyudi; Muslichah Erma Widiana; Basuki Widodo; Soehardjoepri Soehardjoepri; Kamiran Kamiran; nur Asiyah; Meidyta Sinantryana Widyaswari (LPPM of NAROTAMA UNIVERSITY, 2021)
Community service programs based on science and technology as a medium for mentoring prospective entrepreneurs in Rangkah district. Tambak Sari Kenjeran Surabaya, East Java. As partners are craftsmen of Various srundeng and sambal and young people who have connections as entrepreneurs from various groups in the target areas of the activity. The problem faced is that all this time the roasting process of srundeng and sambal sprinkles uses the conventional method, namely by using a frying pan that contains oil so it is unhealthy because it causes cholesterol and easily changes aroma. In carrying out the business activities of making srundeng and sambal sprinkled with sea fish, partners have not applied science and technology as well as potential entrepreneur partners. Many young people from various backgrounds in Rangkah Kenjeran Surabaya which has links as entrepreneurs but no one has yet facilitated assistance. As a solution for this community service program is to use a roaster with a capacity of 15kg / hour with dimensions specifications: 133x63x110cm, fuel: LPQ, 450watt electricity, 220v, to increase production capacity. Second, given training in mentoring concept knowledge and understanding of socio-spiritual and technological insight into marketing activities. Furthermore, providing training on creativity and innovation in the manufacture of products from marine fish from the Kenjeran coastal area to activity partners. The methods of implementation are (1) design, build, maintenance and use of roaster machines (2) training, practice, and assistance to increase conceptual competence and understanding of social and spiritual marketing for partners. (3) Training, practice, and mentoring transmit the mindset and behavior of an entrepreneur to students so that they behave and be entrepreneurial for partners. The results of this activity show a positive impact in improving the quality of partner products and increasing understanding, especially in entrepreneurship in improving their business going forward.